Approaches to facilitate the socialization of the educable mentally retarded children (primary level) - San Miguel, Mercedes T. (1972)
The purpose of the study was to identify the effective approaches in developing socialization among the educable mentally retarded children in the primary level. The study is a result of library researches. The findings of different authorities helped in the logical selection and organization of ideas, which served as the frame of reference in the setting up of original activities in the social training of the educable mentally retarded children in the primary level. Another social training is the sociometric system. A sociogram can be used by the teacher to detect and discover children who cause friction. Knowing the result, the teacher modifies and improves the classroom management so that effective teaching-learning situation can be achieved.